2018
DOI: 10.1002/joc.5562
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends reveal decreasing intensity of daily precipitation in Spain

Abstract: A comprehensive analysis of the spatial and temporal variability of daily precipitation in Spain in the period 1950-2012 was carried out based on the high-resolution gridded data set SPREAD at a 5 × 5 km spatial resolution. Temporal trends of 12 daily precipitation indices were computed by application of the Sen's slope and the Mann-Kendall tests. The spatial distribution of the trends showed (a) a global slight increase in the duration of the precipitation events, especially along the Mediterranean fringe; (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 60 publications
1
23
0
6
Order By: Relevance
“…The largest rainfall events (consecutive rainy days) amounted to 230.0 mm in 2009, 176.8 mm in 2012, and 167.0 mm in 2004 (Table 1). Daily rainfall has been increasing in the Mediterranean (Ribes et al, 2019) although not in all the regions (Serrano-Notivoli et al, 2018) were found the same trend. The highest rainfall events show a good correlation with the highest mean annual rainfall at the study area such as has also been found in other research sites (Mathbout et al, 2018) (Fig.…”
Section: Rainfallmentioning
confidence: 78%
“…The largest rainfall events (consecutive rainy days) amounted to 230.0 mm in 2009, 176.8 mm in 2012, and 167.0 mm in 2004 (Table 1). Daily rainfall has been increasing in the Mediterranean (Ribes et al, 2019) although not in all the regions (Serrano-Notivoli et al, 2018) were found the same trend. The highest rainfall events show a good correlation with the highest mean annual rainfall at the study area such as has also been found in other research sites (Mathbout et al, 2018) (Fig.…”
Section: Rainfallmentioning
confidence: 78%
“…This is often observed in water-limited environments, as is the case in much of the IP, where precipitation does not always cause significant changes in soil moisture evolution [71,72], especially when it is analyzed at the scale of the entire soil profile due to the existence of certain decoupling between the atmosphere and the soil system [73]. The increase in the frequency of low-precipitation events detected in Spain in recent decades [74] could also affect this dynamic.…”
Section: Resultsmentioning
confidence: 99%
“…These results are supported by several regional studies. Some of these studies report no change, or decrease in erosivity in NW Mediterranean areas ( Angulo-Martínez and Beguería 2012 ; Beguería et al 2018 ; Serrano-Notivoli et al 2018 ), but also the opposite trend for Chinese landscapes ( Xin et al 2011 ). These trends identified by regional studies are in line with the ones found by our study.…”
Section: Discussionmentioning
confidence: 99%